HUBUNGAN USIA PERTAMA MENSTRUASI (MENARCHE) DAN RIWAYAT KELUARGA DENGAN KEJADIAN DISMENORE PADA REMAJA PUTRI KELAS VIII DI SMPN I GADINGREJO KECAMATAN GADINGREJO KAB. PRINGSEWU TAHUN 2016 - Puspita , Linda; Kesuma Wardani , Psiari (Jurnal Kelitbangan Bappeda Pringsewu, 2017)
Menstrual pain (dysmenorrhea) is a cramping and sharp pain that feels on the lower abdomen and thighs, lower back. Types of menstrual pain are primary and secondary, primary dysmenorrhea usually occurs below 20 years. The knowledge of adolescent reproductive health that lacks an anxiety attitude and assumes a negative attitude towards menstruation. One of the causes of dysmenorrhea is the age of menstruation (menarche) and family history. Knowledge of the prevalence of menstrual first age and family history with dysmenorrhea incidence, so that adolescents have knowledge of the causes of primary dysmenorrhea. This research was conducted at SMPN 1 Gadingrejo District Pringsewu. The design of this study was analytic, with a Cross-sectional study design. The subject of this research is adolescent daughter of class VIII. The data collected were the number of first menstrual ages and family history with the incidence of dysmenorrhea. The highest frequency distribution of first menstruation age was â‰¤12 years old 38 students (61,3%), family history most family history 35 (56,5%), and dysmenorrhoea 33 (53,2) %). There is a significant relationship between the first age of menstruation and family history. The result of statistic test between menstrual age with dysmenorrhea incidence was 0.003 < value of Î± 0,05. Statistical test result between family history and dysmenorrhea incidence was 0.001 < Î± 0,05